Povyshenie effektivnosti podgotovki bortsov greko-rimskogo stilya na osnove ispol'zovaniya tekhnicheskikh sredtsv razvitiya spetsial'noi gibkosti - Abulkhanov, A. N.; Martyanov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study was to reveal the specifics of wrestlers' flexibility in some situations ofwrestling. The index of special stength-flexibility was formalized. The complex of technical means, providing the cooperative development of special physical qualities was elaborated. The high efficiency of the methodics was proved by the significant increase of the main indicies in physical and technical-tactic preparadeness. The technology of the methodic's using is represented in practical recommendations.